Battling with Swords and Shields: a Semantic Analysis of the Paradox of Belonging and Performing in a Cooperative - Felix, Bruno (Organizações & Sociedade, 2021)
This study aimed to understand how the semantic analysis of the process of (re)construction of organizational narratives can help a cooperative to manage paradoxical goals. We performed a single case study based on in-depth interviews with 47 employees, non-participant observations, and document analysis in a Brazilian credit cooperative. Our results showed that individuals may tell stories to influence others’ sensemaking of “what is going on here.” When such stories show semantic fit with the linguistic organizational context, they become able to shape others’ sensemaking. As different and competitive stories can coexist, they can reflect both polarized (e. g., “we are financial-centered” versus “we are social-centered”) and paradoxical self-definitions (“we are financial-and-social-centered”). Thus, the semantic element of organizational narratives not only highlights the dialogical nature of organizations but also their paradoxical nature.